Developing the Children's Literature Teaching Materials Based on Wisdom of Local Area to Improve the Students’ Learning Outcomes - Rahayu, Enny; Febriyana, Mutia; Artha, Dewi Juni (Budapest International Research and Critics University, 2021)
This research aims to develop the teaching material products in the form of children's literature text books based on the wisdom of local area. This research method uses a Research and Development (R&D) using the ADDIE development model to develop the teaching materials for the children's literature based on wisdom of local area (North Sumatra) which consists of the analysis, design, development, implementation, and evaluation stages. The sample in this study was the fifth grade students of SD (primary school) of Swasta Muhammadiyah 12 Medan in Medan. The results proved that the students’ learning outcomes in children's literature increased after using teaching materials based on local area wisdom (North Sumatra). The average score of the students before using teaching materials was 68, meanwhile the average value of the students after using teaching materials was 82. The test scores for the children's literature appreciation learning outcomes obtained an average score of 79.2. The results of the calculation through the t test by using SPSS test showed a significant result before and after using the teaching materials. It can be concluded that the teaching materials for the children's literature based on local area wisdom (North Sumatra) are appropriate for the students to use.